Work and family in the new economy - Ammons, Samantha K.; Kelly, Erin L. (Erin Lee), 1970- (Bingley, U.K. : Emerald, 2015)
This volume will focus on innovative research that examines how the nature of paid work intersects with family and personal life today. Although some workers have more stability than others, rising income inequality, the continued rise of nonstandard work, further erosion of unions, technological advancements that encourage permeable boundaries between work and home, and the pressures of a global 24/7 economy generate an aura of insecurity for all. Some workers are working long hours but have some control over when, where and how they work; many others are poorly compensated and struggle with underemployment, have little say over their schedules, lack adequate benefits, and must cobble together several jobs and/or rely heavily on kinship networks to make ends meet. These changes suggest the need for nuanced analyses that are sensitive to class variation in work conditions and to diverse family formations. Research that addresses how current work conditions are experienced in different life course stages and in different policy contexts is also needed to fully understand the work-family interface.
Italian parents in precarious work : how normative beliefs affect social understandings of the work-family boundary / Anna Carreri -- The second shift and the nonstandard shift : how working nonstandard hours affects the relationship between the division of household labor and wives' fairness perceptions / Katie James, Jody Clay-Warner -- Technology use and the new economy : work extension, network connectivity, and employee distress and productivity / Noelle Chesley, Britta E. Johnson -- What would Jesus haul? Home, work and the politics of masculinity among Christian long-haul truck drivers / Rebecca L. Upton -- Policing work and family : how workers cope with contradictions and dilemmas of implementing welfare-to-work / Tiffany Taylor -- When work becomes family : the case of low wage caregivers / Naomi Gerstel, Dan Clawson -- Is work-family conflict a multi-level stressor linking job conditions to mental health? Evidence from the work, family and health network / Phyllis Moen ... [et al.] -- The relationship of work unit pressure to satisfaction with work-family balance : a new twist on negative spillover? / Jacquelyn Boone James ... [et al.] -- Giving care and perceiving discrimination : the social and organizational context of family responsibilities discrimination / Lindsey Trimble OConnor, Julie A. Kmec, Elizabeth C. Harris -- Policy or empowerment? Policy environments, political empowerment and work-family conflict / Leah Ruppanner -- Discussing work-life fit : factors that predict managerial promotion of flexible work arrangements / Stephen Sweet, Jacquelyn Boone James, Marcie Pitt-Catsouphes -- Implementing institutional change : flexible work and team processes in a white collar organization / Kelly Chermack ... [et al.].
Print version record
Keywords: Social Science -- Sociology / Marriage & Family; Sociology: family & relationships; Sociology: work & labour; Work and family